Cookies Berbahan Umbi Gembili sebagai Inovasi Pangan yang Bernilai Ekonomi, Kaya Gizi, dan Menyehatkan - Nadella Ervietasari1 (Universitas Duta Bangsa Surakarta, 2021)
In the millennial era, various unhealthy foods have emerged, which have an impact on health problems such as heart disease, cancer and diabetes to various segments of the population. Realizing the seriousness of this problem, government policies that support healthy living and preventive measures against this disease are often taken, one of which is by making functional food. Functional food is food that naturally or through processes, contains one or more compounds which, based on the results of scientific studies, are considered to have certain physiological functions that are beneficial to health. Gembili tubers can be an alternative formaterials for making functional foods such as cookies. Gembili tubers (Dioscorea esculenta) are included in the local tubers which contain 14.629% inulin content. Inulin can reduce the risk of colon cancer, normalize blood sugar levels and help with heart health and prevent colon cancer. This study aims to determine the use of gembili tubers into cookies as a functional food that has economic value, is rich in nutrients, and is healthy. This research method is carried out by studying literature that searches databases of various references, such as research journals, journal reviews, annual reports, books and data related to the use of gembili tubers as functional foods published in 2009-2019. Data analysis was obtained, compiled, and analyzed so as to get conclusions about the literature study research. The results of this literature study state that food products from gembili flour have a relatively crispy texture and do not contain gluten, so they are not suitable for processed products that require high volume development. However, gembili tuber flour contains dietary fiber that the body needs, even containing higher inulin than that in wheat.